2011
DOI: 10.1089/ten.tea.2010.0516
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Concentrate and Bovine Bone Mineral for Sinus Floor Augmentation: A Controlled, Randomized, Single-Blinded Clinical and Histological Trial—Per-Protocol Analysis

Abstract: NBF after 3-4 months is equivalent in sinus, augmented with BMAC and BBM or a mixture of AB and BBM. This technique could be an alternative for using autografts to stimulate bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
109
1
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(122 citation statements)
references
References 39 publications
4
109
1
8
Order By: Relevance
“…To list a few, MSCs have been incorporated with hydroxyapatite/TCP scaffolds for the reconstruction of calvarial and alveolar bone in mice and dogs [De Kok et al, 2003;Mankani et al, 2006], seeded into microporous gelatin scaffold for the regeneration of calvarial defects in mice [Krebsbach et al, 1998], combined with PLA-based scaffolds to repair cranial bone defects in rabbits [Bidic et al, 2003], and loaded on hyaluronan-based scaffold in order to regenerate orbital rim defects in pigs [Radice et al, 2000]. MSCs with or without scaffold and osteogenic factors have been used for many sinus augmentation surgeries in many clinical trials [Gimbel et al, 2007;Pelegrine et al, 2010;Sauerbier et al, 2010;Rickert et al, 2011;Sauerbier et al, 2011;Hermund et al, 2012;Kaigler et al, 2013]. In addition, MSCs have been used by different delivery approaches in other craniofacial defects caused by traumatic bone defect, osteomyelitis, and tumor resection ( Table 2 ).…”
Section: Mscs For Treating Oral and Craniofacial Bone Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…To list a few, MSCs have been incorporated with hydroxyapatite/TCP scaffolds for the reconstruction of calvarial and alveolar bone in mice and dogs [De Kok et al, 2003;Mankani et al, 2006], seeded into microporous gelatin scaffold for the regeneration of calvarial defects in mice [Krebsbach et al, 1998], combined with PLA-based scaffolds to repair cranial bone defects in rabbits [Bidic et al, 2003], and loaded on hyaluronan-based scaffold in order to regenerate orbital rim defects in pigs [Radice et al, 2000]. MSCs with or without scaffold and osteogenic factors have been used for many sinus augmentation surgeries in many clinical trials [Gimbel et al, 2007;Pelegrine et al, 2010;Sauerbier et al, 2010;Rickert et al, 2011;Sauerbier et al, 2011;Hermund et al, 2012;Kaigler et al, 2013]. In addition, MSCs have been used by different delivery approaches in other craniofacial defects caused by traumatic bone defect, osteomyelitis, and tumor resection ( Table 2 ).…”
Section: Mscs For Treating Oral and Craniofacial Bone Injuriesmentioning
confidence: 99%
“…In addition, MSCs have been used by different delivery approaches in other craniofacial defects caused by traumatic bone defect, osteomyelitis, and tumor resection ( Table 2 ). Most clinical trials in oral and craniofacial bone repair have reported promising results [Gimbel et al, 2007;Pelegrine et al, 2010;Sauerbier et al, 2010;Rickert et al, 2011;Sauerbier et al, 2011;Kaigler et al, 2013]; however, no statistically significant results were found in one clinical trial [Hermund et al, 2012]. Such controversial results may be rooted in the various technical errors.…”
Section: Mscs For Treating Oral and Craniofacial Bone Injuriesmentioning
confidence: 99%
“…There have been limited reports on the effect of bone marrow cells in distraction osteogenesis [30,45,55]. In 2007, Richards et al [47] observed marrow-derived progenitor cell injections enhanced new bone formation in a femoral distraction model of rat. In 2007, Kitoh et al [30,31] showed transplantation of culture-expanded bone marrow cells combined with PRP accelerated new bone formation during the distraction osteogenesis, especially in the femur, but with many disadvantages [47].…”
Section: Discussionmentioning
confidence: 99%
“…They found that HGF-loaded scaffolds promoted mineralisation, angiogenesis, new bone formation and β-TCP absorption [20]. Sauerbier et al [21] and Rickert et al [22] performed randomised controlled clinical trials to investigate formation of new bone in patients with severe atrophy of the maxillary sinus. Patients obtained an augmentation of the sinus from bovine bone material either with BMAC or autologous bone.…”
Section: Discussionmentioning
confidence: 99%